2022
DOI: 10.3390/biom12060853
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam as a Probe for Heterotropic Drug-Drug Interactions Mediated by CYP3A4

Abstract: Human cytochrome P450 CYP3A4 is involved in the processing of more than 35% of current pharmaceuticals and therefore is responsible for multiple drug-drug interactions (DDI). In order to develop a method for the detection and prediction of the possible involvement of new drug candidates in CYP3A4-mediated DDI, we evaluated the application of midazolam (MDZ) as a probe substrate. MDZ is hydroxylated by CYP3A4 in two positions: 1-hydroxy MDZ formed at lower substrate concentrations, and up to 35% of 4-hydroxy MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 72 publications
2
23
0
Order By: Relevance
“…In our current work, TST is considered as a probe to investigate the heterotropic allostery in MDZ metabolism, which has the strongest allosteric effect on the MDZ metabolism as reported by Denisov et al Our results indicate that the presence of TST can promote the transition of the MDZ binding mode through long-range allosteric effects and can also increase the formation of 4-OH-MDZ. The work of Denisov et al 60 is a timely event that can provide experimental data to support our current study, and the important role of the F′−F loop reported by Denisov et al is also clarified by us that the movement of the F′−F loop can expand the CYP3A4 active site volume and open the "sandwich" structure providing favorable conditions for the transition of the MDZ binding mode. In this work, we propose two potential allosteric sites (Site 1 and Site 2) located in the periphery of CYP3A4, and we also discuss in detail that Site 2 seems to be more pronounced than Site 1 as it is modulated by three regulatory pathways.…”
Section: Regulation Of Mdz Metabolism By Tst Binding In Sitesupporting
confidence: 81%
See 3 more Smart Citations
“…In our current work, TST is considered as a probe to investigate the heterotropic allostery in MDZ metabolism, which has the strongest allosteric effect on the MDZ metabolism as reported by Denisov et al Our results indicate that the presence of TST can promote the transition of the MDZ binding mode through long-range allosteric effects and can also increase the formation of 4-OH-MDZ. The work of Denisov et al 60 is a timely event that can provide experimental data to support our current study, and the important role of the F′−F loop reported by Denisov et al is also clarified by us that the movement of the F′−F loop can expand the CYP3A4 active site volume and open the "sandwich" structure providing favorable conditions for the transition of the MDZ binding mode. In this work, we propose two potential allosteric sites (Site 1 and Site 2) located in the periphery of CYP3A4, and we also discuss in detail that Site 2 seems to be more pronounced than Site 1 as it is modulated by three regulatory pathways.…”
Section: Regulation Of Mdz Metabolism By Tst Binding In Sitesupporting
confidence: 81%
“…The effects caused by TST binding can remotely promote the transition of the MDZ binding mode in the CYP3A4 active site via multiple allosteric communication pathways, which can increase the probability of pose C and facilitate the formation of 4-OH-MDZ. These findings could help us to understand the experimental fact 12,60 that TST can stimulate the formation of 4-OH-MDZ. According to the results of the residue interaction network (RIN), many key residues involved in the allosteric communication pathways are recognized; among them, R105 and F108 as well as heme are identified as key factors to trigger the transition of the MDZ binding mode.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…As mentioned above, membrane proteins can be reconstituted in a detergent-free lipid environment. Amphipathic MSP-based [ 80 , 81 , 82 ] and peptide-based [ 83 ] nanodiscs are commonly used systems for studying membrane proteins in the desired lipid environment [ 84 , 85 ]. However, the MSP protein or peptide in the nanodisc belt can interfere with the membrane protein characterization by many biophysical techniques, including circular dichroism (CD) and ultraviolet-visible (UV) absorption spectroscopy techniques.…”
Section: Challenges With the Purification And Reconstitution Of Membr...mentioning
confidence: 99%